PENILAIAN MASYARAKAT MENGENAI AKUNTANSI KEUANGAN PUBLIK DAN AKUNTANSI PERUSAHAAN - Hurian Kamela (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2024)
The public's assessment of public financial and corporate accounting still needs to be improved because the average public only knows about accounting in general. The objectives of this research are (1) To provide an analysis of the public's assessment of the differences between public financial accounting and corporate accounting quantitatively and (2) To analyze public knowledge regarding the differences in accounting assessments at the private and government levels. This research uses primary data (questionnaire) to make the research results quantitative. The research population is the people of the Jabodetabek area. The sample consisted of 110 people. Data was collected for 1 month, October 2024, using a questionnaire. The research model uses multiple regression analysis. The analysis technique uses purposive sampling. The research results (1) show that the public still needs to understand the differences between government and corporate accounting, especially in organizations; (2) people's behaviour is only appropriate to where they work, not caring about intentions to seek information about accounting developments.